Peningkatan Kualitas Sumber Daya Manusia Melalui Pelatihan Soft skill Pada SMA Dharma Pancasila Medan - Lubis, Dewi Shinta Wulandari; Soraya Grabiella Dinamika; Riandani Rezki Prana; Tri Utari Ismayuni; Vidya Fathimah (Yayasan Literasi Sains Indonesia, 2022)
Soft skills are very important in addition to academic knowledge. Soft skills are also non-technical abilities such as being able to think critically and time management. In the world of work, companies are not only looking for prospective employe with good hard skills but also for the soft skills they have. This is very important to be socialized and give knowledge to students in high school because they are the future successors of the nation who will enter the world of lectures and work, to improve their quality. One thing that can be done is the Community Service Training (PKM) activity entitled 'Improving the Quality of Human Resources Through Soft skill Training' where the participants of this activity consist of students from SMA Dharma Pancasila Medan. The methods given are briefing, presentation, discussion, case study, and final evaluation. This activity aims to provide understanding and mastery of soft skills to improve the quality of human resources. The result of this activity concluded that this activity was very helpful for participants in increasing their understanding and awareness of improving soft skills.